Inside Cover: Nonplanar Butterfly‐Shaped π‐Expanded Pyrrolopyrroles (Chem. Eur. J. 46/2016). Issue 46 (26th September 2016) - Krzeszewski, Maciej; Kodama, Takuya; Espinoza, Eli M.; Vullev, Valentine I.; Kubo, Takashi; Gryko, Daniel T.
Abstract : Heterocyclic nanographenes come in different sizes and shapes. Gryko, Kubo, Vullev and co‐workers have discovered that π‐expansion of pyrrole[3, 2‐ b ]pyrroles leads to double helical heterocycles, the shape of which reminds of butterflies. The energy barrier between the folded meso form and two enantiomers in the twisted form is low, which allows co‐existence of "natural‐shaped" and "non‐natural" butterflies. These centrosymmetric compounds are solvatofluorochromic, which points to symmetry breaking in the excited state. More information can be found in the Full Paper by V. I. Vullev, T. Kubo, D. T. Gryko et al. onpage 16478 ff.